New experimental approaches enabling the continuous monitoring of gas species in hydrothermal fluids - Giroud, Sébastien; Tomonaga, Yama; Brennwald, Matthias S.; Takahata, Naoto; Shibata, Tomo; Sano, Yuji; Kipfer, Rolf (Frontiers in Water, 2023)
Hot thermal fluids flow through the Earth's crust and carry valuable information about the deep subsurface. The monitoring of natural tracers transported in geothermal fluids, such as gases or ions, are relevant to better understand the geological processes in the Earth's subsurface and their relation to deep fluid dynamics. Recently developed technologies (e.g., portable gas-equilibrium membrane-inlet mass spectrometry) allow for the continuous monitoring of gas species at a much higher temporal resolution than the sampling procedures commonly used, based on a few individual samples. However, the monitoring of gas species from hot thermal fluids still poses experimental challenges tied to unwanted water vapor condensation in the headspace of the separation module, which irremediably leads to clogging (e.g., of the connecting capillaries) and failure of the detection device. In this contribution, we present two new experimental methods that provide suitable technical conditions to measure gases, even in high temperature geothermal fluids, using a portable gas analyzer. Two sites with different thermal water temperatures (first one ranging from 50 °C to 65 °C and second one close to boiling temperature) were selected. The first method was deployed on the thermal waters of Lavey-les-Bains (Vaud, Switzerland), for which we report results from October 2021. The second method was used in Beppu (Oita Prefecture, Japan), for which we report results from April 2018. Our results show that at both sites, our methods allow for continuous measurements of gas species (N2, Ar, O2, Kr, He, CH4, CO2 and H2) in thermal waters. Furthermore, they show that the variability of gas emanation from the two sites can only be adequately described by measurements with high temporal resolution, which both methods allow.